Adoptive Cell Therapy: A Novel and Potential Immunotherapy for Glioblastoma - Wang, Jingyu; Shen, Fang; Yao, Ying; Wang, Lin-lin; Zhu, Yongjian; Hu, Jue (Frontiers in Oncology, 2020)
Glioblastoma multiforme (GBM) is the most common primary brain tumor in adults with very poor prognosis and few advances in its treatment. Recently, fast-growing cancer immunotherapy provides a glimmer of hope for GBM treatment. Adoptive cell therapy (ACT) aims at infusing immune cells with direct anti-tumor activity, including tumor-infiltrating lymphocyte (TIL) transfer and genetically engineered T cells transfer. For example, complete regressions in patients with melanoma and refractory lymphoma have been shown by using naturally tumor-reactive T cells and genetically engineered T cells expressing the chimeric anti-CD19 receptor, respectively. Recently, administration of ACT showed therapeutic potentials for GBM treatment as well. In this review, we summarize the success of ACT in the treatment of cancer and provide approaches to overcome some challenges of ACT to allow its adoption for GBM treatment.